MODERNIZATION OF FIXED ASSETS OF BUSINESS ENTITIES IN THE AGRICULTURAL SECTOR UNDER THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - KRYUKOVA, Irina; IHNATENKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Increasing the strategic competitiveness of domestic agrarian business under current and future conditions is impossible without considering the principles and values of sustainable development. Among the key factors that provide the possibility of transition to sustainable agribusiness models in agriculture is the quantitative and qualitative state of fixed assets. Modernization of fixed assets is a complex process, the management of which in agricultural management faces a significant number of problematic aspects, in particular: lack of financial resources and difficulties in finding investment sources, the import origin of a substantial part of agricultural machinery, a long-term military conflict, the presence of logistical and infrastructure problems, the level of digitalization and innovation in agriculture, climate and environmental challenges in agribusiness.The article identifies key priorities for the modernization of fixed assets of agricultural business entities that consider the principles of sustainable development of agriculture and rural areas. The main requirements for managing the modernization process of fixed assets based on sustainability are outlined. Among them are functional requirements for equipment and technology, which provide for the minimization (absence) of harmful impacts on the environment; energy efficiency; compliance with current environmental standards; automation and intelligence of the management system; and cost-effectiveness.An analysis of the dynamics of the cost and share of fixed assets in Ukrainian agriculture was conducted. The results showed a positive trend in the growth of agricultural producers' fixed asset costs. The coefficient of renewal of fixed assets in 2023 was 9%.The author's vision of the model of measurements of the sustainability of technical modernization of agricultural business is proposed, including economic, environmental, and social sustainability. Promising types of farming machinery are identified, making agrarian business modernization possible because of sustainable development. Among them are proposed: tractors for precision farming, electric vehicles, technical means and tools for precision farming, agricultural machinery based on renewable energy, Smart drip irrigation systems, battery-powered hand tools, farm equipment, and regenerative farming equipment.
Keywords: fixed capital; agriculture; technical support; agricultural machinery; ecologization; agricultural formations